O duplo vínculo (midiático e religioso) nos circuitos-ambientes do pastoreio midiatizado - Cortes, Dinis Ferreira (Universidade do Vale do Rio dos Sinos, 2017)
The research presented in this text is projected within the field of studies on the mediatization of religion. The objectives of this research are: a) to map the media, circuits, environments and devices configured from the religious institution in the process of building their audiences in mediatic processes; b) identify the socio-anthropological processes triggered in the interactions between religious institution, media logics, actors and devotees; c) to deduce about the semiosis constituted in the interactions between mediated, mediatized institutions and actors. As research delimitation, we will use the environment built from the Associação Filhos do Pai Eterno (AFIPE) and his mentor Father Robson de Oliveira. This environment includes: the Pai Eterno program and Novena dos Filhos do Pai Eterno program transmitted from Rede Vida de Televisão; social networks Facebook and Instagram; the YouTube streaming site; the official website of AFIPE; letters sent to members; and mobile applications. The research method is presented in three arguments: first, the construction of the research case, inferred in abductive processes; Second, the deduction, understood as immersion in the empirical ones from propositions presented; Third, the induction, consolidating epistemological inferences from the empirical analyzes. The epistemological inferences are presented in three dimensions: the anthropological bases identified in the interactions; The semiosis driven in the analyzed circuit-environment; And mediatization and circulation as a conclusive perspective for understanding the constructed object. We highlight from the results that the media-interaction processes establish a relationship between the devotees and the Church that suggest a mutualism, where descended from the promise of healing through the institution (Church), function in articulation with the media recognition from the upward participation of the Devotees, in the environment constituted from AFIPE. Through processes of use and appropriation of the speeches of devotees in digital networks, e-mails, letters and interviews, inferential understandings of the present order are observed: narratives and discursive semiotics; the media as a configuration of induced narratives; mediatization as a power device; and the process of interactional transit based on selection and tentative regulatory control.
Keywords: Circulação midiática; Mutualismo; Narratividades induzidas; Regulação tentativa; Midiatização; Induced narrativities; Media circulation; Mediatization; Mutualism; Tentative regulation; ACCNPQ::Ciências Sociais Aplicadas::Comunicação